Honeycomb-like carbon nitride through supramolecular preorganization of monomers for high photocatalytic performance under visible light irradiation. (November 2018) - Huang, Jinhui; Cheng, Wenjian; Shi, Yahui; Zeng, Guangming; Yu, Hanbo; Gu, Yanling; Shi, Lixiu; Yi, Kaixin
Abstract: A metal-free modified carbon nitride MCU(DMSO)-C3 N4 (3:3:1) with a honeycomb-like morphology was prepared via firstly introducing cyanuric acid and urea into melamine in dimethyl sulfoxide (DMSO) as the precursor for the MCU-C3 N4 . A variety of characterization methods, including XRD, XPS, FT-IR, SEM, TEM, UV–vis, photoluminescence (PL), and photocurrent generation, were applied to investigate the structure, morphology, optical, and photoelectrochemical properties of the g-C3 N4 and MCU-C3 N4 (3:3:1). Rhodamine B (RhB), methylene blue (MB), and bisphenol A (BPA) were selected as target pollutants to evaluate photocatalytic activity of the MCU-C3 N4 (3:3:1) under visible light irradiation. MCU-C3 N4 (3:3:1) exhibits significantly enhanced photocatalytic activity compared with g-C3 N4, where 99.49% RhB is removed within 40min, 97.7% MB is removed within 80 min, and 84.37% BPA is removed within 90 min. The improved photodegradation efficiency was mainly due to the larger surface area, the stronger REDOX ability, and the increased separation efficiency of photogenerated electron-hole pairs. The active radical trapping experiments and electron spin resonance tests indicated that h + and O2 − radicals were the dominant active species whereas OH radicals could be a minor factor. A possible photocatalytic mechanism is proposed. This strategy here provides an ideal platform for the design of photocatalysts with large surface area and high porosity for various pollutant controlling applications. Highlights: Honeycomb-like MCU-C3 N4 (3:3:1) is well prepared by molecular self-assembly. High-surface area of MCU-C3 N4 improves the photoinduced charges separation. MCU-C3 N4 has greater improvements in degradation of RhB, MB and BPA than g-C3 N4 . This preparation strategy for MCU-C3 N4 (3:3:1) is facile and environment-friendly.